La dimensione socio-ambientale dello sviluppo integrale delle aziende: Il ruolo delle piccole imprese meridionali tra società civile e criminalità organizzata - La Rosa, Fabio (Piccola Impresa / Small Business, 2010)
Over the last few years scholars theorized different frameworks to explain causal determinants of the development and success of the firms. Such frameworks have a generalist view, but they play a relevant role also through their single dimensions. In this paper, after a short review of the nature of the relationship between the firm and the environment, with special attention to the role of the society, we adopt the recent framework labeled as comprehensive development(“sviluppo integrale”), and we focus on one of its four key dimensions, the social-environmental one. Indeed, this perspective allows us to emphasize a new role for the small firms: to exploit and to promote the social-environmental context and, particularly, the society. In this sense, small firms should establish a virtuous relationship with the society, rather than having an inert role merely restricted to coexist and to respect it or, worse, aimed to create a connivance relationship with it. In order to provide a real picture of the comprehensive development, we report the interesting experience of some Southern Italy small firms and of a no-profit association (named “Addiopizzo”) – as “representative” of the community – that has the aim to make them free from the mafia protection racket. So, stressing the relevance of the couple “freedomaccountability” in any social-environmental setting, we outline the positive dynamics of this comprehensive development that involves, at this time, only few entrepreneurs really comprehensive accountable according to the framework adopted. The paper concludes trying to detect some drivers (or causal determinants) of the entrepreneurs’ comprehensive development process, useful to explain further cases.